Evaluation of Plasma Assisted Noninvasive Surgery (PANIS) As a New Approach for the Treatment of Conjunctival Concretions: A Clinical Case Series - Nejat, Farhad; Jadidi, Khosrow; Eghtedari, Shima; Nabavi, Nazanin-Sadat; Malekifar, Pooneh (International Journal of Innovative Research in Medical Science, 2021)
Background and Objective: Plasma is one of the newest therapies recently used. This study aimed to evaluate a quick treatment modality of conjunctival concretions using plasma as a noninvasive procedure. Methods: Six eyes of six patients with conjunctival concretions were evaluated. The procedure was performed using plasma spots generated by the white handpiece of the Plexr device. The eyelid was everted and concretions sublimated by plasma spots from the upper and lower eyelids. Refractive Errors, visual acuity (BCVA and UCVA), Ocular Surface Disease Index (OSDI), and Intraocular pressure (IOP) were measured before and after six months of the procedure. Results: The results of 6 months follow-up show that this effective method had no recurrence or side effects. Treatment was effective in all of the patients. No complication and recurrence was observed. The OSDI score was improved to the normal range. This method had no effects on Refractive Errors, Visual Acuity, and IOP. Conclusion: Based on the results, it seems that the PANIS method can be used as a practical, quick, and straightforward approach for the treatment of conjunctival concretions.